A says to B,”I am twice as old as you were when ,I was as old as you are”. the sum of their present age 63 years then, their present ages ar

Question

A says to B,”I am twice as old as you were when ,I was as old as you are”. the sum of their present age 63 years then, their present ages are?​

in progress 0
Ruby 5 days 2022-01-14T21:15:42+00:00 1 Answer 0 views 0

Answers ( )

    0
    2022-01-14T21:17:05+00:00

    Step-by-step explanation:

    Given :

    • A says to B,”I am twice
    • the sum of their present age 63 years

    To Find :

    • present ages are?

    A was as old as B is now (A – B) years ago.

    A = 2 (B – (A – B))

    = 2 (2B – A)

    = 4B – 2A

    3A = 4B

    A + B = 63

    A = 63 – B

    4B = 189 – 3B

    7B = 189

    B = 27

    A = 63 – 27 = 36

    3A = 189 – 3B

    A + B = 63.

    • Hence A was 27 (9 years ago), B was 27 – 9 = 18. And A is 2 x 18 = 36.

Leave an answer

Browse

14:4+1-6*5-7*14:3+5 = ? ( )